EMG based continuous thumb-tip force model for prostheses design - Siddiqi, Abdul Rahman; Sidek, Shahrul Na'im (IIUM Press, International Islamic University Malaysia, 2017)
Human hand functions range from precise-minute handling to heavy and robust movements. Remarkably, 50 percent of all hand functions are made possible by the thumb. Therefore, developing an artificial thumb which can mimic the actions of a real thumb precisely is a major achievement. Most of the development in this area is based on discontinuous thumb position models, which makes it challenging to recreate several of the most important functions of the thumb and also does not result in total imitation. This work looks into the classification of Electromyogram (EMG) signals from thumb muscles for the prediction of thumb force and angle during flexion motion. For this purpose, an experimental setup is developed to measure the thumb angle and force throughout the range of flexion and simultaneously gather the EMG signals. A ‘piecewise- discretization’ approach is used for continuous angle prediction, where the full motion is divided into four segments or classes. For variation in force, the experimental setup is designed to accommodate different weight sets which require application of different thumb-tip force values from the thumb. The EMG signals are taken from four different muscles that are most engaged in the flexion motion. These are the Opponens Pollicis, Flexor Pollicis Brevis, Extensor Pollicis and the First Dorsal Interosseous.